(untitled) (American International Journal of Biology and Life Sciences, 2019)
The aim of this work is to introduce bacteria into the matrix of natural phosphate to catalyze the phenol oxidation in the wastewater.This electrode, designated subsequently by bacteria-NP-CPE, Showed stable response and was characterized with voltammeter methods, as cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and DRX. The experimental results revealed that the prepared electrode could be a feasible for degradation of hazardous phenol pollutants in the wastewater.